Accessing Statistics Canada Health Data at McMaster - Kitchen, Peter; Jadon, Vivek (My University, 2018)
In this session, we will highlight some key data sets and resources related to health that are available through Statistics Canada’s Research Data Centre (RDC) and Data Liberation Initiative (DLI) programs. We will also briefly talk about Real Time Remote Access (RTRA) program, which allows researchers to remotely access various micro data sets at Stat Can. Moreover, in a 90-minute session, we plan to discuss how RDC, DLI and RTRA programs differ from one another in terms of data availability, data access restrictions and requirements.
Keywords: Statistics Canada, Health data, Research Data Centre, Data Liberation Initiative, CIHI